Flight Stability of Canard-Guided Dual-Spin Projectiles with Angular Rate Loops - Qiushi Zheng; Zhiming Zhou (International Journal of Aerospace Engineering)
Generally, as a precision-guided weapon, the missile has many disadvantage such as high price, difficult maintenance, and low yield. Modern war requires more and more new guided ammunition with high precision, low cost, and low collateral damage. Therefore, as a simple guided conventional ammunition technology, the dual-spin projectile has attracted the attention of ammunition experts recently. This paper proposes a dual-spin projectile scheme based on the rotation control method. Firstly, the concept of the dual-spin projectile is introduced. Secondly, the mathematical model of the dual-spin projectile is established, and the angular motion equation is finally obtained by using some linearized assumptions. Finally, the sufficient and necessary conditions of coning motion stability for dual-spin projectile with angular rate loops are analytically derived and further verified by numerical simulations. It is noticed that the upper bound of the control gain is affected by the delay angle of the control system and the spinning rate of the projectile.